PENGARUH ORANG TUA DEMOKRATIS DAN DISIPLIN BELAJAR TERHADAP PRESTASI HASIL BELAJAR PPKN SISWA SD - Yerina Andrianti; Eko Handoyo (Akademika, 2023)
The aim of this research is to obtain an overview of the influence of democratic parenting and learning discipline on PPKn learning outcomes among students at SDN Dolopo 01, Madiun Regency. This research uses a quantitative approach, with a type of correlation research and is used to research certain populations or samples, sampling techniques are generally carried out randomly, data collection uses research instruments, quantitative data analysis with the aim of testing the hypothesis that has been applied, data processed using the SPSS program. Based on the results of research on the influence of democratic parenting and learning discipline on the PPKn learning outcomes of students at SDN Dolopo 01 Madiun Regency, researchers can draw conclusions regarding three things related to the problem formulation, namely: there is a significant influence between democratic parenting on students' PPKn learning achievement. SDN Dolopo 01 Madiun Regency, significance of 0.146, significance level (α) of 0.000<0.05. There is a significant influence between learning discipline on the PPKn learning achievement of students at SDN Dolopo 01 Madiun Regency, the significance is 0.000, which means it can be seen that tcount (6.626) > ttable (1.668) and the significance level (α) is 0.000 < 0.05, and there is There is a significant influence between democratic parenting and learning discipline on the learning achievement of Civic Education students at SDN Dolopo 01 Madiun Regency.